The Role of ATP in Mechanically Stimulated Rapid Closure of the Venus's Flytrap - Jaffe, M. J. (1973)
When the midribs of untreated traps of Dionaea muscipula are frozen in liquid nitrogen after rapid closure, they contain significantly less ATP than those frozen before closure. Exogenous ATP causes a significant increase in the rate of mechanically stimulated trap closure. Illuminated traps close faster than those kept in the dark. The traps of plants placed in 100% O(2) close much faster than do air controls, while 100% CO(2) inhibits closure. It is concluded that ATP is probably the native source of potential energy for contraction of the trap's midrib, and that if the endogenous ATP titer is increased by oxidative phosphorylation or an exogenous source, the trap will close faster.